The urgency of optimizing police brigadier education and training to improve police work professionalism - Fadli Sudria Vera; Nizwardi Jalinus; Syahrial Bachtiar (Global Econedu, 2022)
Crime in Indonesia is increasing day by day, education and training of Indonesian National Police brigadiers are urgently needed to create adequate human resources to reduce crime. This study aims to analyze the education and training program at the Padang Besi State Police School (SPN). This study uses a mix of quantitative and qualitative methods with a 4-stage model of Kircpatrick's evaluation level, namely reaction level, learning level, behavior level, and outcome level. The application of Kirkpatrick's four-level model which is carried out systematically in education and training evaluation activities at the Padang Besi State Police School (SPN) can be one solution, especially for apparatus-based training, so it is hoped that the training evaluation activity can answer one of the evaluation functions, namely to Strengths and weaknesses in the training program can be identified so that improvements can be immediately followed up.